Penerapan Sistem Informasi Akuntansi Pada Usaha Kedai Kopi: Studi Kasus Corak Coffee - Inda Sari, Fadlia; Arizah, Ainun (STIE AMKOP, 2025)
The growth of coffee shop businesses in Indonesia, including in Makassar, has increased rapidly and has contributed to the local economy. However, business actors, especially those at the MSME level, still face various obstacles in managing finances in an organized and systematic manner. This study aims to analyze the implementation of an accounting information system (AIS) at the Corak Coffee coffee shop and to redesign the transaction recording flow to improve operational efficiency and the quality of financial reports. The method used is a case study with a qualitative approach, through direct interviews with business owners. The results of the study show that although Corak Coffee has not used special accounting software, business owners routinely use Microsoft Excel as a medium for recording financial transactions. The income and expense cycles are recorded manually but remain organized, and the resulting financial information has been used as a basis for making business decisions. These findings prove that the application of basic AIS principles, although still simple, can have a positive impact on business management. This study also recommends that MSME actors start considering the use of a more integrated recording system to improve operational accuracy and efficiency. Kata kunci : Accounting Information System, Coffee Shops, Financial Records, Operational Efficiency, UMKM